Tales of inspiration - Chong, Eric. (Petaling Jaya : EMPIRE, 2010)
Successful stories of small business entrepreneurs in Malaysia.
Keywords: Businesspeople -- Malaysia -- Biography; Businessmen -- Malaysia -- Biography; Businesswomen -- Malaysia -- Biography; Success in business -- Malaysia; Small business -- Malaysia; Entrepreneurship -- Malaysia